Hemoperfusion as an Adjuvant Therapy in Maintenance Hemodialysis Patients with Severe COVID-19: A Single Centre Experience - Elizabeth Yasmine Wardoyo; Anggraini Permata Sari; Aryan Y Djojo; Johanes Sarwono; Md Ikhsan Mokoagow; Nikko Darnindro; Jerry Nasarudin; Marina Epriliawati; Annela Manurung; Martha Iskandar; Krishna Adi Wibisana; Anak Agung Arie Widyastuti; et al. (Acta Medica Indonesiana)
Mortality rate among maintenance hemodialysis (HD) patients with COVID-19 is alarmingly high. In Fatmawati General Hospital, most of HD patients with COVID-19 presented with acute respiratory distress syndrome (ARDS). Hemoperfusion (HP) is a blood purification therapy used to remove cytokines and inflammatory mediators to prevent ARDS worsening and organ failure. We report 6 cases of COVID-19 in maintenance HD patients. HP and HD were performed in two consecutive days when patient developed early ARDS as indicated by inflammatory markers elevation. HP and HD were conducted by using resin-containing cartridge and high-flux dialyzer, respectively, for 4 hours. Improvements in CRP levels, PaO2/FiO2 ratios, and chest X-rays were observed after 2 sessions of HP in most of our patients. Based on our clinical experience, the timing of HP delivery is critical and should be undertaken in the early phase of ARDS, but larger studies are still needed.